EVOLUTION OF THE ETHNOSPECIFIC CONCEPT FLEISS (DILIGENCE) IN THE GERMAN LINGUISTIC CULTURE - T.S. Medvedeva; D.I. Medvedeva (Многоязычие в образовательном пространстве)
The paper represents the analysis of the ethnospecific concept Fleiß in the German linguistic culture, it aims at studying the evolution of the concept . An integrated approach is used in which the etymology of the concept’s name and its synonyms have been analysed, as well as the notional component of the concept through the generalisation of the German-language lexicographic data; moreover, the interpretative analysis of proverbs and sayings, and the association and receptive experiments with German informants have been carried out. The evolution of the concept is traced back since the Middle Ages until present time, based on linguistic data and the evidence of the allied humanities. The notional core of Fleiß includes the following characteristics: ‘continuous effort’ , ‘striving for activity’ , ‘intensity of work’ , ‘concentration’ , ‘ambition’ , ‘persistence in pursuing a goal’ . The study reveals that most of the original characteristics in the conceptual core have been preserved, but during the evolution process, which lasted for centuries, some new characteristics appeared. Our research leads to the conclusion that mostly positive connotations of the lexemes representing the concept have remained unchanged, as well as the concept’s high value in the German linguistic culture on the whole. However, the association and receptive experiments revealed that new negative connotations appear in the associations given by some interviewees of the younger generation in the 21st century.